Posthuman transgression of boundaries in Octavia Butler’s Kindred - Czerniakowski, Maciej (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study adopts a critical posthuman perspective to investigate how Octavia Butler’s Kindred aims to reconstruct and later dismantle binary oppositions that have been part and parcel of oppressive systems of power such as slavery. Opening his essay with a brief theoretical outline of posthumanism and transhumanism, the author then strives to elaborate on the conceptual framework of the essay and the relevance of the discussion of slavery. Through the main part of the essay, the author focuses on Butler’s primary objective, which is to problematise the stereotypical relationship between the enslaved and the enslaver, united by fear and rape, to demonstrate that slavery—in a sense—oppressed them both. The author contends that Butler constructs various borderlands founded on binary oppositions to reveal the arbitrariness of the latter so that a posthuman relational cyborg body can emerge. As the author concludes, this symbiotic body becomes a site of transgression in which all boundaries eventually topple over.